Merchandising jako instrument tworzenia przewagi konkurencyjnej w usługach agroturystycznych - Śnihur, Janusz (Merchandising as Instrument of Creation of Competitive Superiority in Agritouristic Services, 2006)
The process of satisfying consumer's needs is undergoing serious changes, also in the field of tourist services. The consumer perceives the agritourist services not only in terms of spending free time, relaxing and having some rest. It is also seen as an opportunity to get to know the specific character of the region and its inhabitants, and as a result its tradition also in the form of regional food and cultural goods. In the following article the reasons for introducing the new forms of marketing - namely merchandising - to suit the needs of agritourist offer are presented. Marketing is still evolving, also in terms of agritourist services, and it should be perceived as an instrument of both promotion and competitive advantage.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 418-428